EVALUATION OF AGRIBUSINESS MANAGEMENT IN RED TILAPIA FISH CULTIVATION (CASE STUDY IN THE NGUDI MAKMUR NGARGOREJO ASSOCIATION) - Purwani, Dian Septi; Setiyani, Rahmawati; Sepfrian, Bimoseno (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Evaluation of Agribusiness Management in Red Tilapia fish Cultivation (Case Study in the Ngudi Makmur Ngargorejo Association) aims to increase production yields and increase income in red tilapia cultivation. This association has only been running for approximately 2 years since mid-2023. The current obstacle experienced by the Ngudi Makmur Ngargorejo Association is that the marketing process is carried out individually and almost all of them do not use standard bookkeeping records. This study aims to determine the marketing efficiency carried out in red tilapia cultivation in the Ngudi Makmur Ngargorejo Association. The analysis method study is marketing method margin analysis with several calculations. There is two channels in marketing: marketing channel level zero besides that the first-level marketing channel. Conclusion results marketing margin the analysis can be shown from the two marketing channels carried out by red tilapia cultivators in the Ngudi Makmur Ngargorejo Association, the zero-level channel is more efficient, namely direct farmer sales to consumers. Therefore, red tilapia production using KJA can be continued and its marketing channels can be developed